2021
DOI: 10.3390/jcm10040572
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Velamentous Cord Insertion Prenatally Diagnosed in Twin Pregnancy

Abstract: Background: The purpose of this study was to evaluate the prevalence of velamentous cord insertion (VCI) and the actual association between pathologically confirmed VCI and perinatal outcomes in twins based on the chorionicity. Methods: All twin pregnancies that received prenatal care at a specialty clinic for multiple pregnancies, from less than 12 weeks of gestation until delivery in a single institution between 2015 and 2018 were included in this retrospective cohort study. Results: A total of 941 twins wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…117 Lee et al recently studied pathologically confirmed velamentous cord insertions and perinatal outcomes of 941 sets of twins with prenatal sonographic diagnosis, according to chorionicity. 116 The prevalence of velamentous insertion in dichorionic twins and monochorionic twins was 5.8% and 7.8%, respectively (P = 0.251). The prevalence of vasa previa and placenta accreta sequence was higher among patients with versus those without velamentous insertion (P = 0.008 and 0.022, respectively).…”
Section: Velamentous Insertion In Twinsmentioning
confidence: 96%
See 1 more Smart Citation
“…117 Lee et al recently studied pathologically confirmed velamentous cord insertions and perinatal outcomes of 941 sets of twins with prenatal sonographic diagnosis, according to chorionicity. 116 The prevalence of velamentous insertion in dichorionic twins and monochorionic twins was 5.8% and 7.8%, respectively (P = 0.251). The prevalence of vasa previa and placenta accreta sequence was higher among patients with versus those without velamentous insertion (P = 0.008 and 0.022, respectively).…”
Section: Velamentous Insertion In Twinsmentioning
confidence: 96%
“…The incidence of velamentous insertion is increased among twin gestations. 106,107,116 Associated adverse perinatal outcomes of velamentous cord insertion among twins are reportedly higher than those associated with singleton gestations. 107 Fries et al in 1993 studied 38 cases of monochorionic-diamniotic twins were identified, 11 of which manifested as twin-twin transfusion syndrome.…”
Section: Velamentous Insertion In Twinsmentioning
confidence: 99%
“…However, we found that MCI was not an independent risk factor for birth weight differences in MCDAs, which is consistent with Lee. [14] Previous studies have shown that the incidence of MCI is about 8.5% in all pregnancies, 6.3% in singleton pregnancies and 10.9% in twin pregnancies, which is more common than VCI. [15] It is thought to be associated with different risk factors, such as pregnancy hemorrhage, advanced maternal age, pregnancies conceived with the aid of artificial reproductive technology, maternal chronic diseases and substance abuse during pregnancy.…”
Section: Discussionmentioning
confidence: 98%
“…However, some studies with relatively large sample sizes have drawn conflicting conclusions about the relationship between abnormal umbilical cord insertion in MCDAs and BWD and sFGR. Lee et al [ 14 ] evaluated the prevalence of VCI in twins and the actual association between pathologically proven VCI and perinatal outcomes based on choriostomy. Nine hundred and forty-one twins were included in the study, and the prevalence of VCI in DCDAs and MCDAs was 5.8% and 7.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation